THE INFLUENCE OF SOCIAL MEDIA AND MARKETING CONTENT ON PURCHASE INTENTION FOR NUFACE PRODUCTS ON TIKTOK SHOP: A CASE STUDY OF STUDENTS AT AS-SYAFI'IYAH ISLAMIC UNIVERSITY - Chusnah, Chusnah; Sugiana, Ugi (Kinerja, 2025)
This study aims to test "The Influence of Social Media and Marketing Content on purchase intention in Nuface Products on TiktokShop at As-syafi'iyah Islamic University" The sample in this study amounted to 140 respondents. The research uses Validity Test, Reliability Test, Normality Test, Multicollinearity Test, and Heteroscedasticity Test. Analysis In the study using Multiple Regression Analysis, Multiple Correlation Analysis, Coefficient of Determination and Hypothesis Test. The results of the T-Test study showed that the Social Media Variable (X1) had a Positive and Significant Effect on purchase intention (Y) with a T- Table Calculation value of > (2.131 > 1.977) and a sig value > α value (0.035 < 0.05). Marketing Content (X2) has a positive and very significant effect on purchase intention (Y) with a Calculated Value of > Ttable (4.058 > 1.977) and a Sig Value > α Value (0.000 < 0.05). The correlation value is 0.718 which means that it shows a strong relationship. The value of the determination coefficient given by Social Media (X1) and Marketing Content (X2) to purchase intention (Y) was 51.7% and the remaining 48.3%, influenced by other factors that were not analyzed.